Species-Specific miRNAs in Human Brain Development and Disease - Prodromidou, Kanella; Matsas, Rebecca (Frontiers in Cellular Neuroscience, 2019)
Identification of the unique features of human brain development and function can be critical towards the elucidation of intricate processes such as higher cognitive functions and human specific pathologies like neuropsychiatric and behavioral disorders. The developing primate and human CNS is distinguished by expanded progenitor zones and a protracted time course of neurogenesis, leading to the expansion in brain size, prominent gyral anatomy, distinctive synaptic properties and complex neural circuits. Comparative genomic studies have revealed that adaptations of brain capacities may be partly explained by human specific genetic changes that impact on the function of proteins associated with neocortical expansion, synaptic function and language development. However, the formation of complex gene networks may be most relevant for brain evolution. Indeed, recent studies identified distinct human specific gene expression patterns across developmental time occurring in brain regions linked to cognition. Interestingly, such modules show species-specific divergence and are enriched in genes associated with neuronal development and synapse formation whilst also being implicated in neuropsychiatric diseases. microRNAs represent a powerful component of gene-regulatory networks by promoting spatiotemporal post-trascriptional control of gene expression in the human and primate brain. It has also been suggested that the divergence in miRNA expression plays an important role in shaping gene expression divergence among species. Primate-specific and human-specific miRNAs are principally involved in progenitor proliferation and neurogenic processes but also associate with human cognition, and neurological disorders. Human embryonic or induced pluripotent stem cells and brain organoids, permitting experimental access to neural cells and differentiation stages that are otherwise difficult or impossible to reach in humans, are an essential means for studying species specific brain miRNAs. Single cell sequencing approaches can further decode the refined miRNA-mRNA interactions during developmental transitions. Elucidating species-specific miRNA regulation will shed new light into the mechanisms that control spatiotemporal events during human brain development and disease, an important step towards fostering novel, holistic and effective therapeutic approaches for neural disorders. In this review we discuss species specific regulation of miRNA function, its contribution in the evolving features of the human brain and in neurological disease, with respect also to future therapeutic approaches.